The triple bind of single-parent families Resources, employment and policies to improve well-being - Nieuwenhuis, Rense; Maldonado, Laurie (Policy Press, 2018)
This edited collection examines the risks and issues faced by single parent-families and their children such as poverty, wealth/asset accumulation, health, well-being and combinative development, bringing together scholars from diverse social science backgrounds, including sociology, economics, political science, and social work.This book is the first collection of studies to examine previously neglected social policies related to single-parent families and provides innovative outcomes that will improve the lives and well-being of single parents and their children.